Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

Let [tex]$f(x)=\frac{6 \sin x}{2 \sin x + 4 \cos x}$[/tex].

1. Find [tex]$f^{\prime}(x)$[/tex]:
[tex]f^{\prime}(x) = \square[/tex]

2. The equation of the tangent line to [tex][tex]$y = f(x)$[/tex][/tex] at [tex]$a = \frac{\pi}{4}$[/tex] can be written in the form [tex]$y = mx + b$[/tex], where:
[tex]\[
\begin{array}{l}
m = \square \\
b = \square
\end{array}
\][/tex]

(Note: Ensure to compute the derivatives and the tangent line equation using the given function and point.)


Sagot :

To solve the given problem, let's break it down into several steps.

1. Find [tex]\( f'(x) \)[/tex] - the derivative of [tex]\( f(x) \)[/tex] using the quotient rule.
2. Evaluate the derivative at [tex]\( a = \frac{\pi}{4} \)[/tex] to find the slope of the tangent line.
3. Find the value of the function at [tex]\( a = \frac{\pi}{4} \)[/tex].
4. Find the equation of the tangent line using the point-slope form of a line.

Let's start from the top.

### Step 1: Finding [tex]\( f'(x) \)[/tex]

Given the function:
[tex]\[ f(x) = \frac{6 \sin x}{2 \sin x + 4 \cos x} \][/tex]

We use the quotient rule for differentiation:
[tex]\[ f'(x) = \frac{u'v - uv'}{v^2} \][/tex]
where [tex]\( u = 6 \sin x \)[/tex] and [tex]\( v = 2 \sin x + 4 \cos x \)[/tex].

First, we find the derivatives of [tex]\( u \)[/tex] and [tex]\( v \)[/tex]:
[tex]\[ u' = 6 \cos x \][/tex]
[tex]\[ v' = 2 \cos x - 4 \sin x \][/tex]

Applying the quotient rule:
[tex]\[ f'(x) = \frac{(6 \cos x)(2 \sin x + 4 \cos x) - (6 \sin x)(2 \cos x - 4 \sin x)}{(2 \sin x + 4 \cos x)^2} \][/tex]

Simplify the numerator:
[tex]\[ \text{Numerator} = 6 \cos x (2 \sin x + 4 \cos x) - 6 \sin x (2 \cos x - 4 \sin x) \][/tex]
[tex]\[ = 12 \cos x \sin x + 24 \cos^2 x - 12 \sin x \cos x + 24 \sin^2 x \][/tex]
[tex]\[ = 24 \cos^2 x + 24 \sin^2 x \][/tex]
[tex]\[ = 24 (\cos^2 x + \sin^2 x) \][/tex]
[tex]\[ = 24 \][/tex]

Note: The actual derived formula from the solution is a symbolic representation. Here we have:
[tex]\[ f'(x) = \frac{6 \cos x (2 \sin x + 4 \cos x) + 6 (4 \sin x - 2 \cos x) \sin x}{(2 \sin x + 4 \cos x)^2} \][/tex]

Thus:
[tex]\[ f'(x) = \frac{6\cos(x)}{2\sin(x) + 4\cos(x)} + \frac{6(4\sin(x) - 2\cos(x))\sin(x)}{(2\sin(x) + 4\cos(x))^2} \][/tex]

### Step 2: Evaluate the derivative at [tex]\( a = \frac{\pi}{4} \)[/tex]

We need to find [tex]\( f'(\pi/4) \)[/tex].

From the result:
[tex]\[ f'(\frac{\pi}{4}) = 1.33333333333333 \][/tex]

So, the slope [tex]\( m \)[/tex] of the tangent line at [tex]\( x = \frac{\pi}{4} \)[/tex]:
[tex]\[ m = 1.33333333333333 \][/tex]

### Step 3: Find [tex]\( f\left(\frac{\pi}{4}\right) \)[/tex]

Evaluate [tex]\( f(x) \)[/tex] at [tex]\( x = \frac{\pi}{4} \)[/tex]:
[tex]\[ f(\frac{\pi}{4}) = \frac{6 \sin(\frac{\pi}{4})}{2 \sin(\frac{\pi}{4}) + 4 \cos(\frac{\pi}{4})} \][/tex]
[tex]\[ = \frac{6 \cdot \frac{\sqrt{2}}{2}}{2 \cdot \frac{\sqrt{2}}{2} + 4 \cdot \frac{\sqrt{2}}{2}} \][/tex]
[tex]\[ = \frac{6 \cdot \frac{\sqrt{2}}{2}}{ \frac{2\sqrt{2}}{2} + \frac{4\sqrt{2}}{2}} \][/tex]
[tex]\[ = \frac{6 \cdot \frac{\sqrt{2}}{2}}{ \sqrt{2} + 2\sqrt{2}} \][/tex]
[tex]\[ = \frac{3\sqrt{2}}{ 3\sqrt{2}} = 1 \][/tex]

So, the value [tex]\( f \left( \frac{\pi}{4} \right) = 1 \)[/tex].

### Step 4: Find the equation of the tangent line

We use the point-slope form of a line equation:
[tex]\[ y - y_1 = m (x - x_1) \][/tex]

Where [tex]\( m = 1.33333333333333 \)[/tex], [tex]\( x_1 = \frac{\pi}{4} \)[/tex], and [tex]\( y_1 = 1 \)[/tex].

Rearrange to the slope-intercept form [tex]\( y = mx + b \)[/tex]:
[tex]\[ y = 1.33333333333333 x + b \][/tex]

Now, calculate [tex]\( b \)[/tex]:
[tex]\[ 1 = 1.33333333333333 \cdot \frac{\pi}{4} + b \][/tex]
[tex]\[ b = 1 - 1.33333333333333 \cdot \frac{\pi}{4} \][/tex]

From the result, [tex]\( b = 1.0 - 0.333333333333333\pi \)[/tex].

Putting it together:
- The slope [tex]\( m = 1.33333333333333 \)[/tex].
- The y-intercept [tex]\( b = 1.0 - 0.333333333333333\pi \)[/tex].

Thus, the equation of the tangent line is:
[tex]\[ y = 1.33333333333333x + 1.0 - 0.333333333333333\pi \][/tex]